International Topics in Central America S Thought and Agenda, 1900-2010. a Framework in Five Moments - Deves-Valdes, E (Universidad de Talca, 2016)
Between the beginning of the 20th century and 2010 several moments can be noted in the discussion of Central American thought and in the creation of an agenda in regards to international and world affairs, revealing some topics and concepts that are sustained throughout the century, while others are renewed. This paper establishes a chronological framework of five moments in the development of ideas, focusing on the most relevant concepts and the protagonists in the discussions. It attempts to highlight what distinguishes Central American works from those elaborated in other regions of Latin America.